In situ phase separation ionogel adhesives, methods of making and use thereof
Patent Information
- Application Number
- CN202311402367.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-10-26
AI Technical Summary
[0003]然而不仅是离子凝胶,大多数凝胶的机械性能都很弱,因为液体含量高,导致内聚力差
[0029]与现有技术相比,本申请的有益效果包括:
Smart Images

Figure CN117447642B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of materials, and in particular to an in-situ phase-separated ion gel adhesive, its preparation method, and its application. Background Technology
[0002] Adhesives play a vital role in our daily lives and modern industries, including the medical, construction, automotive, marine, aerospace, robotics, and wearable devices sectors. The bonding ability between two substrates is crucial for adhesives, making the development of high-performance adhesives one of the most popular research topics for many years. The performance of an adhesive is primarily determined by two factors: interfacial adhesion to other substrates and its internal cohesive force. Interfacial adhesion mainly stems from the strength of various interactions between the adhesive and the substrate, such as van der Waals forces, hydrogen bonds, ionic bonds, metal coordination bonds, dipole-dipole, ion-dipole, and other non-covalent or chemically covalent bonds. Cohesive force is a manifestation of the adhesive's internal energy dissipation capacity. When the adhesive is subjected to external forces, its internal components or structure dissipate external energy, thereby preventing damage and increasing strength. Ionic gels are obtained by swelling a polymer network in an ionic liquid, and their structure is similar to that of hydrogels. Ionic liquids possess thermal stability, electrochemical stability, and are essentially non-volatile, making them a focus of attention in various fields. In particular, the presence of a large number of ions in its structure can not only generate interactions within the polymer network and enhance its own cohesive force, but also form ionic bonds or ion-dipole interactions with certain matrices to enhance interfacial adhesion. Therefore, it shows great potential as an adhesive.
[0003] However, not only ionic gels, but most gels have weak mechanical properties due to their high liquid content, which leads to poor cohesion. Summary of the Invention
[0004] The purpose of this application is to provide an in-situ phase-separated ion gel adhesive, its preparation method, and its application, in order to solve the above-mentioned problems.
[0005] To achieve the above objectives, this application adopts the following technical solution:
[0006] A method for preparing an in-situ phase-separated ion gel adhesive, comprising:
[0007] A precursor solution is obtained by dissolving a monomer, an initiator, and a crosslinking agent in an imidazole ionic liquid, and the precursor solution is reacted to obtain the in-situ phase-separated ion gel adhesive.
[0008] The monomers include monomers that are soluble in ionic liquids and monomers that are insoluble in ionic liquids. The monomers that are soluble in ionic liquids include first acrylate monomers, and the monomers that are insoluble in ionic liquids include one or more of second acrylate monomers, acrylamide monomers, and methacrylate monomers.
[0009] Preferably, the first acrylate monomer includes one or more of methyl acrylate, ethyl acrylate, butyl acrylate, octyl ethyl acrylate, tetrafluoroethyl acrylate, hexafluorobutyl acrylate, polyethylene glycol methyl ether acrylate, methyl methacrylate, hydroxyethyl methacrylate, and polyethylene glycol methyl ether methacrylate.
[0010] The second acrylate monomer includes acrylic acid and / or α-methacrylic acid, the acrylamide monomer includes acrylamide and / or N,N-dimethylacrylamide; the methacrylate monomer includes benzyl methacrylate and / or tert-butyl methacrylate.
[0011] Preferably, the imidazole ionic liquid includes one or more of 1-methyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.
[0012] Preferably, the initiator includes one or more of photoinitiators, thermal initiators, and redox initiators;
[0013] The photoinitiator includes one or more of the following: 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphosphonate, 2-methyl-1-[4-methylthiophenyl]-2-morpholinyl-1-propanone, 2-isopropylthioxanthone, ethyl 4-dimethylaminobenzoate, 1-hydroxy-cyclohexylphenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, benzoin dimethyl ether, methyl o-benzoylbenzoate, 4-chlorobenzophenone, 4-phenylbenzophenone, and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone;
[0014] The thermal initiator includes one or more of azoisobutyronitrile, 4,4'-azo(4-cyanopenic acid), azobisisobutyramide hydrochloride, and benzoyl peroxide.
[0015] The redox initiator includes one or more of hydrogen peroxide / ferrous salt, ammonium persulfate / tetramethylethylenediamine, potassium persulfate / sodium sulfite, and benzoyl peroxide / N,N-dimethylaniline.
[0016] Preferably, the crosslinking agent includes one or more of the following: multifunctional acrylate crosslinking agents, multifunctional acrylamide crosslinking agents, multifunctional styrene crosslinking agents, and multifunctional vinyl crosslinking agents;
[0017] The multifunctional acrylate crosslinking agent includes one or more of the following: poly(ethylene glycol) diacrylate, poly(ethylene glycol) methyl diacrylate, 1,3-propanediol diacrylate, 1,4-butanediol diacrylate, and 1,6-hexanediol diacrylate.
[0018] The multifunctional acrylamide crosslinking agent includes methylenebisacrylamide;
[0019] The multifunctional styrene-based crosslinking agent includes divinylbenzene;
[0020] The multifunctional vinyl crosslinking agent includes diethylene glycol divinyl ether.
[0021] Preferably, the reaction includes photoinitiation, thermal initiation, and redox initiation;
[0022] The photoinitiation condition is a light source power density of 1-1000 mW / cm³. 2 Wavelength 200-450nm, duration 0.01-24h;
[0023] The conditions for thermal initiation are 60-80℃ for 2-24 hours;
[0024] The conditions for initiating the redox reaction are 0-40℃ for 2-24 hours.
[0025] Preferably, the mass ratio of the monomer of the corresponding polymer that is soluble in ionic liquid to the monomer of the corresponding polymer that is insoluble in ionic liquid is 1:(0.1-10).
[0026] Preferably, the mass ratio of the monomer, the imidazole ionic liquid, the initiator, and the crosslinking agent is 1:(0.1-7):(0.1-5%):(0-10%).
[0027] This application also provides an in-situ phase-separated ionogel adhesive, which is prepared using the method described above.
[0028] This application also provides an application of an in-situ phase-separated ion gel adhesive for use in the medical field, construction industry, automotive field, marine industry, aerospace field, robotics and wearable devices.
[0029] Compared with the prior art, the beneficial effects of this application include:
[0030] The in-situ microphase separation ionogel adhesive provided in this application utilizes in-situ microphase separation and combines it with numerous dynamic interactions such as hydrogen bonds, ionic bonds, and ion-dipole bonds in the system to simultaneously enhance cohesive and interfacial adhesion, thereby achieving a novel method for ultra-strong adhesive performance in ionogel adhesives. By copolymerizing two monomers in an ionic liquid, the significant difference in compatibility between the polymers corresponding to the two monomers in the ionic liquid leads to in-situ microphase separation. The polymer segments with good compatibility mostly dissolve in the ionic liquid, forming a solvent-rich phase, while the polymer segments with poor compatibility aggregate due to solvent repellency, forming polymer-rich phase domains. When the ionogel is subjected to external forces, the polymer-rich phase dissipates the external energy, while the solvent-rich phase ensures the deformability of the ionogel, thus enhancing the overall cohesive energy and overall mechanical properties of the ionogel adhesive. The numerous hydrogen bonds, ionic bonds, and ion-dipole dynamic interactions within ionogels not only enhance their cohesive energy but also foster interactions with various substrates, thereby strengthening their surface adhesion. Ionogels prepared by combining in-situ phase separation with multiple dynamic interactions exhibit unprecedented adhesive properties.
[0031] The in-situ microphase separation ionogel adhesive preparation method provided in this application is simple, convenient, and highly practical. It utilizes in-situ microphase separation and numerous non-covalent dynamic interactions within the system to enhance both the adhesive's cohesive force and the interfacial adhesion to the substrate, thereby achieving superior adhesion performance, reaching an adhesion strength of 13.41 MPa on a glass substrate.
[0032] Due to the wide variety of ionic liquids and monomers, countless possibilities and combinations exist for selecting appropriate formulations based on compatibility differences. Furthermore, the excellent non-volatility, non-flammability, thermal stability, and electrochemical stability of ionic liquids allow these adhesives to meet the needs of various fields and application scenarios. Therefore, this type of in-situ microphase-separated ionic gel has promising application prospects in daily life, industry, marine exploration, and aerospace. Attached Figure Description
[0033] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation on the scope of this application.
[0034] Figure 1 The images show physical samples with different monomer ratios when the ionic liquid mass is 40% in Example 1.
[0035] Figure 2 SEM images of samples with different monomer ratios when the ionic liquid mass is 40% in Example 1;
[0036] Figure 3 The adhesion performance test data of samples with different monomer ratios on glass substrates when the ionic liquid mass is 40% in Example 1 is as follows;
[0037] Figure 4 This is the adhesion performance test data of samples with different monomer ratios on glass substrates when the ionic liquid mass is 40% in Example 2. Detailed Implementation
[0038] To fully illustrate the advantages of the technical solution provided in this application, it will first be presented in its overall form, as follows:
[0039] A method for preparing an in-situ phase-separated ion gel adhesive, comprising:
[0040] A precursor solution is obtained by dissolving a monomer, an initiator, and a crosslinking agent in an imidazole ionic liquid, and the precursor solution is reacted to obtain the in-situ phase-separated ion gel adhesive.
[0041] The monomers include monomers that are soluble in ionic liquids and monomers that are insoluble in ionic liquids. The monomers that are soluble in ionic liquids include first acrylate monomers, and the monomers that are insoluble in ionic liquids include one or more of second acrylate monomers, acrylamide monomers, and methacrylate monomers.
[0042] To enhance the strength and toughness of gels, numerous mechanisms have been proposed. The main purpose of these mechanisms is to enhance the gel's ability to dissipate external energy and thus improve cohesion by introducing various interactions at different dimensions of the gel structure. For example, at the molecular level, by selecting specific monomers or fillers, dynamic interactions such as hydrogen bonds, ionic bonds, ion-dipole bonds, and metal coordination can be formed between units and fillers on different polymer chains, and energy dissipation is achieved through the breaking of these dynamic bonds. Furthermore, at the polymer chain level, the application of longer polymer chains induces polymer chain entanglement, so that external energy can be dissipated by untangling when external forces are applied. Finally, at the overall gel structure level, a dual-network structure can be introduced, where the sacrificial network can be destroyed under external forces to dissipate energy, while the main network ensures the integrity of the gel throughout the process. In addition, by introducing phase separation into the gel structure, the polymer-rich phase contributes to energy dissipation, while the solvent-rich phase ensures the gel's deformability, thereby enhancing the gel's energy dissipation capacity. The above toughening mechanisms can be selectively applied to adhesives to further optimize their bonding performance by increasing the cohesive energy of the adhesive.
[0043] In an optional embodiment, the first acrylate monomer includes one or more of methyl acrylate, ethyl acrylate, butyl acrylate, octyl ethyl acrylate, tetrafluoroethyl acrylate, hexafluorobutyl acrylate, polyethylene glycol methyl ether acrylate, methyl methacrylate, hydroxyethyl methacrylate, and polyethylene glycol methyl ether methacrylate.
[0044] The second acrylate monomer includes acrylic acid and / or α-methacrylic acid, the acrylamide monomer includes acrylamide and / or N,N-dimethylacrylamide; the methacrylate monomer includes benzyl methacrylate and / or tert-butyl methacrylate.
[0045] In one optional embodiment, the imidazole ionic liquid comprises one or more of 1-methyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.
[0046] In one optional embodiment, the initiator includes one or more of photoinitiators, thermal initiators, and redox initiators;
[0047] The photoinitiator includes one or more of the following: 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphosphonate, 2-methyl-1-[4-methylthiophenyl]-2-morpholinyl-1-propanone, 2-isopropylthioxanthone, ethyl 4-dimethylaminobenzoate, 1-hydroxy-cyclohexylphenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, benzoin dimethyl ether, methyl o-benzoylbenzoate, 4-chlorobenzophenone, 4-phenylbenzophenone, and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone;
[0048] The thermal initiator includes one or more of azoisobutyronitrile, 4,4'-azo(4-cyanopenic acid), azobisisobutyramide hydrochloride, and benzoyl peroxide.
[0049] The redox initiator includes one or more of hydrogen peroxide / ferrous salt, ammonium persulfate / tetramethylethylenediamine, potassium persulfate / sodium sulfite, and benzoyl peroxide / N,N-dimethylaniline.
[0050] In one optional embodiment, the crosslinking agent includes one or more of the following: multifunctional acrylate crosslinking agents, multifunctional acrylamide crosslinking agents, multifunctional styrene crosslinking agents, and multifunctional vinyl crosslinking agents;
[0051] The multifunctional acrylate crosslinking agent includes one or more of the following: poly(ethylene glycol) diacrylate, poly(ethylene glycol) methyl diacrylate, 1,3-propanediol diacrylate, 1,4-butanediol diacrylate, and 1,6-hexanediol diacrylate.
[0052] The multifunctional acrylamide crosslinking agent includes methylenebisacrylamide;
[0053] The multifunctional styrene-based crosslinking agent includes divinylbenzene;
[0054] The multifunctional vinyl crosslinking agent includes diethylene glycol divinyl ether.
[0055] In one optional implementation, the reaction includes photoinitiation, thermal initiation, and redox initiation;
[0056] The photoinitiation condition is a light source power density of 1-1000 mW / cm³. 2 Wavelength 200-450nm, duration 0.01-24h;
[0057] The conditions for thermal initiation are 60-80℃ for 2-24 hours;
[0058] The conditions for initiating the redox reaction are 0-40℃ for 2-24 hours.
[0059] Optionally, in the photo-initiated conditions, the power density of the light source can be 1 mW / cm². 2 10mW / cm 2 100mW / cm 2 200mW / cm 2 300mW / cm 2 400mW / cm 2 500mW / cm 2 600mW / cm 2 700mW / cm 2 800mW / cm 2 900mW / cm 2 1000mW / cm 2 Or 1-1000mW / cm 2 The wavelength can be any value between 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, or any value between 200-450nm; the time can be any value between 0.01h, 0.1h, 1h, 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, or any value between 0.01-24h; in the thermal initiation conditions, the temperature can be 60℃, 70℃, 80℃, or 60-80℃. The time can be any value between 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h or any value between 2 and 24h; in the conditions for initiating redox reactions, the temperature can be any value between 0℃, 10℃, 20℃, 30℃, 40℃ or 0-40℃, and the time can be any value between 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h or any value between 2 and 24h.
[0060] In an optional embodiment, the mass ratio of the monomer of the corresponding polymer that is soluble in ionic liquid to the monomer of the corresponding polymer that is insoluble in ionic liquid is 1:(0.1-10).
[0061] Optionally, the mass ratio of the monomer of the corresponding polymer that is soluble in ionic liquid to the monomer of the corresponding polymer that is insoluble in ionic liquid can be any value between 1:0.1, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or 1:(0.1-10).
[0062] In one optional embodiment, the mass ratio of the monomer, the imidazole ionic liquid, the initiator, and the crosslinking agent is 1:(0.1-7):(0.1-5%):(0-10%).
[0063] Optionally, the mass ratio of the monomer, the imidazole ionic liquid, the initiator, and the crosslinking agent can be any value between 1:0.1:0.1%:0.1%, 1:1:0.1%:0.1%, 1:5:0.1%:0.1%, 1:7:0.1%:0.1%, 1:0.1:1%:0.1%, 1:0.1:5%:0.1%, 1:0.1:0.1%:1%, 1:0.1:0.1%:5%, 1:0.1:0.1%:10%, 1:1:1%:1%, 1:5:3%:5%, 1:7:5%:10%, or 1:(0.1-7):(0.1-5%):(0-10%).
[0064] This application also provides an in-situ phase-separated ionogel adhesive, which is prepared using the method described above.
[0065] This application also provides an application of an in-situ phase-separated ion gel adhesive for use in the medical field, construction industry, automotive field, marine industry, aerospace field, robotics and wearable devices.
[0066] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.
[0067] Example 1
[0068] Monomers methyl methacrylate (MMA) and acrylic acid (AA), along with the photoinitiator 1-hydroxycycloethylphenyl ketone (184), were dissolved in the ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt (EMITFSI), and the mixture was vibrated and sonicated to form a precursor solution.
[0069] Polymethyl methacrylate (PMMA) exhibits good solubility in EMITFSI, while polyacrylic acid (PAA) shows poor compatibility with EMITFSI. Therefore, the scale of phase separation in the ionogel structure is adjusted by modifying the ratio between the two monomers and the mass ratio between the monomer and the ionic liquid to achieve optimal adhesion performance.
[0070] in Figure 1The diagram shows samples with different monomer ratios when the ionic liquid mass is fixed at 40% (content ratios of 0 and 100 are used as controls). Figure 2 The images shown are their corresponding scanning electron microscope (SEM) images. When the MMA:AA ratio is 6:4, the sample structure exhibits microphase separation, appearing macroscopically homogeneous and slightly translucent. Furthermore, Figure 3 This demonstrates the adhesion performance of this series of iontophoretic adhesives on glass substrates.
[0071] Therefore, the ionic liquid was ultimately determined to account for 40% of the total mass, the mass ratio of monomers MMA to AA was determined to be 6:4, and the mass of photoinitiator 184 was 1% of the total monomer mass. The prepared precursor solution can be injected between the two substrates to be adhered, using a light source with a power density of 900 mW / cm². 2 The ionomer adhesive was irradiated with ultraviolet light at a wavelength of 365 nm for one hour. The prepared ionomer adhesive exhibited excellent adhesion on different substrates (glass 13.41 MPa, ceramic 14.42 MPa, stainless steel 10.70 MPa, aluminum 7.90 MPa, PVC 6.36 MPa, PMMA 2.80 MPa), with a microphase separation scale between 100 and 500 nm.
[0072] Example 2
[0073] Monomers MMA and tert-butyl methacrylate (tBMA), along with photoinitiator 184, were dissolved in the ionic liquid EMITFSI. The mixture was then vibrated and sonicated to ensure homogeneity, forming a precursor solution. PMMA exhibited good solubility in EMITFSI, while tert-butyl methacrylate (PtBMA) showed poor compatibility with EMITFSI. Therefore, the scale of phase separation in the ionic gel structure was adjusted by modifying the ratio of the two monomers and the mass ratio of monomers to the ionic liquid to achieve optimal adhesion performance. Figure 4 The adhesion properties of a series of ionogel adhesives on glass substrates were demonstrated. The final determination was that the ionic liquid comprised 40% of the total mass, the mass ratio of monomer MMA to tBMA was 6:4, and the photoinitiator 184 comprised 1% of the total monomer mass. The prepared precursor solution could be injected between the two substrates to be adhered, using a light source with a power density of 900 mW / cm². 2 The ionogel adhesive was irradiated with ultraviolet light at a wavelength of 365 nm for one hour. The adhesion of the prepared ionogel adhesive to a glass substrate was 3.77 MPa.
[0074] Example 3
[0075] Monomers MMA and acrylamide (MA), along with photoinitiator 184, were dissolved in the ionic liquid EMITFSI. The mixture was vibrated and sonicated to ensure homogeneity, forming a precursor solution. PMMA showed good solubility in EMITFSI, while polyacrylamide (PMA) exhibited poor compatibility with EMITFSI. Therefore, the scale of phase separation in the ionogel structure was adjusted by modifying the ratio of the two monomers and the mass ratio of monomers to the ionic liquid to achieve optimal adhesion performance. The prepared precursor solution could be injected between the two substrates to be adhered, using a light source with a power density of 900 mW / cm². 2 The ionogel adhesive was irradiated with ultraviolet light at a wavelength of 365 nm for one hour. The resulting ionogel adhesive exhibited good adhesion properties on the substrate.
[0076] Example 4
[0077] Monomers MMA and acrylic acid (AA), along with the thermal initiator azoisobutyronitrile (AIBN), were dissolved in the ionic liquid EMITFSI. The mixture was vibrated and sonicated to ensure homogeneity, forming a precursor solution. PMMA exhibited good solubility in EMITFSI, while polyacrylic acid (PAA) showed poor compatibility with EMITFSI. Therefore, the scale of phase separation in the ionogel structure was adjusted by modifying the ratio between the two monomers and the mass ratio of monomers to the ionic liquid to achieve optimal adhesion performance. The prepared precursor solution was injected between the two substrates to be adhered and cured in an oven at 80°C for 6 hours. The resulting ionogel adhesive exhibited good adhesion performance on the substrates.
[0078] Example 5
[0079] Monomers MMA and acrylic acid (AA), along with the redox initiator hydrogen peroxide / ferrous salt, were dissolved in the ionic liquid EMITFSI. The mixture was then vibrated and sonicated to ensure homogeneity, forming a precursor solution. PMMA exhibited good solubility in EMITFSI, while polyacrylic acid (PAA) showed poor compatibility with EMITFSI. Therefore, the scale of phase separation in the ionogel structure was adjusted by modifying the ratio between the two monomers and the mass ratio of monomers to the ionic liquid to achieve optimal adhesion performance. The prepared precursor solution was injected between the two substrates to be adhered and reacted at room temperature for 6 hours. The resulting ionogel adhesive exhibited good adhesion performance on the substrates.
[0080] Comparative Example 1
[0081] To demonstrate that in-situ microphase separation significantly enhances the adhesion performance of iontophoretic adhesives, a homogeneous iontophoretic adhesive without phase separation was prepared. Monomers MMA and hexafluorobutyl acrylate (HFBA), along with photoinitiator 184, were dissolved in the ionic liquid EMITFSI and mixed uniformly by ultrasonic vibration to form a precursor solution. Both PMMA and HFBA were dissolved in EMITFSI. The resulting iontophoretic gel was completely homogeneous and transparent, exhibiting no phase separation in its structure. The reaction conditions were the same as in Example 1. When the ionic liquid mass fraction was 40% and the mass ratio of the two monomers was 1:1, its adhesion performance was less than 2 MPa, significantly lower than that of the in-situ microphase-separated iontophoretic adhesive in this patent.
[0082] Comparative Example 2
[0083] To demonstrate that in-situ microphase separation significantly enhances the adhesion properties of ionomer gel adhesives, a monomer, MMA, and photoinitiator 184 were dissolved in the ionic liquid EMITFSI. The mixture was vibrated and sonicated to ensure homogeneity, forming a precursor solution. The ionic liquid comprised 40% of the total mass. Because PMMA is dissolved in EMITFSI, the resulting pure PMMA ionomer gel exhibited a completely homogeneous and transparent state. The reaction conditions were the same as in Example 1. Figure 1 As shown, and Figure 2 The SEM images show that no phase separation occurs in its structure. Due to the lack of microphase separation reinforcement, its adhesion performance is only 0.73 MPa. Figure 3 As shown, microphase separation significantly improves the adhesion properties of ionogels.
[0084] Comparative Example 3: To demonstrate that in-situ microphase separation significantly enhances the adhesion properties of ionomer gel adhesives, a monomer AA and photoinitiator 184 were dissolved in the ionic liquid EMITFSI. The mixture was vibrated and sonicated to ensure homogeneity, forming a precursor solution. The ionic liquid comprised 40% of the total mass. Since PAA is insoluble in EMITFSI, the resulting pure PAA ionomer gel was completely opaque and white. The reaction conditions were the same as in Example 1. Figure 1 As shown, and Figure 2 The SEM images reveal large-scale phase separation structures within its framework. Excessive phase separation results in poor mechanical properties and a fragile nature, making it unable to bond two substrates together. Figure 3 As shown.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
[0086] Furthermore, those skilled in the art will understand that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of this application and form different embodiments. For example, in the foregoing claims, any of the claimed embodiments can be used in any combination. The information disclosed in this background section is intended only to enhance the understanding of the general background of this application and should not be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing an in-situ phase-separated ion gel adhesive, characterized in that, include: A precursor solution is obtained by dissolving a monomer, an initiator, and a crosslinking agent in an imidazole ionic liquid, and the precursor solution is reacted to obtain the in-situ phase-separated ion gel adhesive. The monomers include monomers that are soluble in ionic liquids and monomers that are insoluble in ionic liquids. The monomers that are soluble in ionic liquids include first acrylate monomers, and the monomers that are insoluble in ionic liquids are tert-butyl methacrylate. The first acrylate monomer is selected from one or more of methyl acrylate, ethyl acrylate, butyl acrylate, octyl ethyl acrylate, and methyl methacrylate; The imidazole ionic liquids include one or more of the following: 1-methyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, 1-propyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt. The mass ratio of the monomer of the corresponding polymer that is soluble in ionic liquid to the monomer of the corresponding polymer that is insoluble in ionic liquid is 1:(0.1-10). The mass ratio of the monomer, the imidazole ionic liquid, the initiator, and the crosslinking agent is 1:(0.1-7):(0.1-5%):(0-10%).
2. The method for preparing the in-situ phase-separated ion gel adhesive according to claim 1, characterized in that, The first acrylate monomer is methyl methacrylate, and the imidazole ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.
3. The method for preparing the in-situ phase-separated ion gel adhesive according to claim 1, characterized in that, The initiator includes one or more of photoinitiators, thermal initiators, and redox initiators; The photoinitiator includes one or more of the following: 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphosphonate, 2-methyl-1-[4-methylthiophenyl]-2-morpholinyl-1-propanone, 2-isopropylthioxanthone, ethyl 4-dimethylaminobenzoate, 1-hydroxy-cyclohexylphenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, benzoin dimethyl ether, methyl o-benzoylbenzoate, 4-chlorobenzophenone, 4-phenylbenzophenone, and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone; The thermal initiator includes one or more of azoisobutyronitrile, 4,4'-azo(4-cyanopenic acid), azobisisobutyramide hydrochloride, and benzoyl peroxide. The redox initiator includes one or more of hydrogen peroxide / ferrous salt, ammonium persulfate / tetramethylethylenediamine, potassium persulfate / sodium sulfite, and benzoyl peroxide / N,N-dimethylaniline.
4. The method for preparing the in-situ phase-separated ion gel adhesive according to claim 1, characterized in that, The crosslinking agent includes one or more of the following: multifunctional acrylate crosslinking agents, multifunctional acrylamide crosslinking agents, multifunctional styrene crosslinking agents, and multifunctional vinyl crosslinking agents; The multifunctional acrylate crosslinking agent includes one or more of poly(ethylene glycol) diacrylate, 1,3-propanediol diacrylate, 1,4-butanediol diacrylate, and 1,6-hexanediol diacrylate. The multifunctional acrylamide crosslinking agent includes methylenebisacrylamide; The multifunctional styrene-based crosslinking agent includes divinylbenzene; The multifunctional vinyl crosslinking agent includes diethylene glycol divinyl ether.
5. The method for preparing the in-situ phase-separated ion gel adhesive according to claim 1, characterized in that, The reactions include photoinitiation, thermal initiation, and redox initiation; The photoinitiation condition is a light source power density of 1-1000 mW / cm². 2 Wavelength 200-450nm, duration 0.01-24h; The conditions for thermal initiation are 60-80℃ for 2-24 hours; The conditions for initiating the redox reaction are 0-40℃ for 2-24 hours.
6. An in-situ phase-separated ion gel adhesive, characterized in that, It is prepared using the preparation method of the in-situ phase separation ion gel adhesive according to any one of claims 1-5.
7. The application of the in-situ phase-separated ion gel adhesive according to claim 6, characterized in that, Used in the construction industry, automotive industry, marine industry, aerospace industry, robotics and wearable devices.
Citation Information
Patent Citations
Underwater automatic adhesion adhesive and preparation method thereof
CN116836656A